2014
DOI: 10.3109/03009742.2013.863381
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of HLA-B27 subtype in patients with ankylosing spondylitis in Northern Norway

Abstract: HLA-B27*05 is the predominant subtype of HLA-B27 in Northern Norway. This supports the concept of a North-South gradient for HLA-B27 subtypes with little regional drive to adapt to environmental challenges. Low-resolution HLA-B27 PCR screening captures all relevant subtypes in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…8,9,16,18 Indeed, relatively few studies performed the profound and prudent exploration of its effects on disease expression or clinical severity of SpA patients. 37,39,41 In the current study, a noticeably male predominance and markedly elevated CRP were found in B*27 positive SpA patients. In multivariable linear regression analysis, the elevated CRP was significantly associated with HLA-B*27 positivity, grade of sacroiliitis, and male gender.…”
Section: Comparisons Between Different Hla-b*27 Subtypessupporting
confidence: 57%
“…8,9,16,18 Indeed, relatively few studies performed the profound and prudent exploration of its effects on disease expression or clinical severity of SpA patients. 37,39,41 In the current study, a noticeably male predominance and markedly elevated CRP were found in B*27 positive SpA patients. In multivariable linear regression analysis, the elevated CRP was significantly associated with HLA-B*27 positivity, grade of sacroiliitis, and male gender.…”
Section: Comparisons Between Different Hla-b*27 Subtypessupporting
confidence: 57%
“…LD analysis (http://www.broadinstitute.org/mpg/snap/ ldsearch.php) using the Broad SNAP tool indicates an R2 of 0.009 and D¢ of 1.00, which makes it unlikely that LD was a significant confounder. Finally, while we failed to establish a link between TNF promoter polymorphism and HLA-B27, this only applies to this white cohort with an almost exclusive presence of the HLA-B27*05 subtype 42 .…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, the Venezuelan population presented the same pattern of association between Hla-B*2705 and Hla-B*2702 subtypes with as (7). There has been found no phenotypic difference regarding the clinical manifestations between the patients with Hla-B*2702 and those with Hla-B*2705 (25). On the other hand, Hla-B*2708 subtype has been found in the majority of healthy Venezuelan controls, and it was absent from the population with as, so this may suggest the association between Hla-B*2708 subtype and the protection against as (26).…”
Section: Hla-b*27 and Spondyloarthritismentioning
confidence: 70%